KARYOTYPIC STUDIES OF FRESHWATER PRAWN MACHROBRACHIUM ROSENBERGII - GOPAL KRISHNA, GOPAL KRISHNA; FOTEDAR, SEEMA; JAIN, ATUL KUMAR (Journal of Indian Fisheries Association, 2015)
Chromosomal studies were conducted on Macrobrachium rose11bergii. On the basis of 50 metaphase plate counts, 38 metacentric, 14 sub metacentric and 66 telocentric chromosomes (2n = 118) were observed. The total length of the genomeÂ was recorded to be 34.2 micron.